In Vivo Studies of Protein Misfolding and Neurodegeneration Induced by Metabolic Syndrome Relative to Chronic Cerebral Hypoperfusion: A Critical Review - Herrera, María I. (2020)
Metabolic syndrome (MetS) leads to microvascular dysfunction and chronic cerebral hypoperfusion (CCH) in an insidious way. Clinical evidence and several rodent models have contributed to determining the neurodegenerative effect of a sustained decrease in cerebral blood flow (CBF). Protein misfolding and aggrega- tion derived from CCH might account for the establishment of vascular cognitive impairment and dementia (VCID) and Alzheimer?s disease (AD). However, the complex and multifactorial etiology of cerebrovascular disease demands the combination of experimental models in scientific research. In this sense, the present work aims at summarizing the differential available rodent paradigms for studying the establishment of cognitive decline resulting from protein misfolding inducedby MetS in association with CCH. Revising experimental findings in the field will help further basic research on the pathophysiology of cerebrovascular disease and the future testing of protein-remodeling factors as neuroprotective agents for the prevention of cognitive impairment.